Cyclotron production of the Ag-105,Ag-106m, Pd-100,Pd-101, Rh-100,Rh-101m,Rh-105 radionuclides by Pd-nat(p,x) nuclear processes - Khandaker, Mayeen Uddin (Elsevier, 2010)
Production cross-sections of the Ag-105g+m,Ag-106m, Pd-100,Pd-101, and Rh-100g+m,Rh-101m.105g+m radionuclides through proton-induced reactions on natural palladium were measured up to 40 MeV by using a stacked-foil activation technique combined with high-resolution gamma-ray spectrometry. The production cross-sections of Pd-101 and Rh-100g+m,Rh-105g+m radionuclides have been reported here for the first time from the Pd-nat(p,x) nuclear processes. The present results are compared with the available literature values as well as the theoretical data calculated by the TALYS and the ALICE-IPPE computer codes. A quantitative comparison of the present results with the theoretical data has also been done with several deviation factor definitions. Optimal production pathways of the therapeutic Rh-105g radionuclide with minimal contamination using cyclotrons are discussed elaborately. (C) 2010 Elsevier B.V. All rights reserved.